2021
DOI: 10.1002/cbdv.202000966
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Guided Investigation of Sideritis cypria Methanol Extract Driven by in Vitro Antioxidant and Cytotoxic Assays

Abstract: Sideritis cypria Post is an endemic and endangered species of Northern Cyprus. The overall aim of the present study was to evaluate the total phenolic content, the antioxidant, the cytotoxic and the antimicrobial activity of the methanol extract obtained from the aerial parts of cultivated S. cypria. A bio‐guided approach led to the isolation of 27 chemical compounds by using various analytical techniques. Their structures were elucidated on the basis of 1D and 2D NMR spectroscopy. The crude extract exerted st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 65 publications
3
17
1
Order By: Relevance
“…Μelittoside ( 2 ) was isolated as a white amorphous powder and its molecular structure C 21 H 32 O 15 was determined by 1 H- & 13 C-NMR, MS, and UV-vis spectra ( Table S2 and Figures S4–S7 ), which agreed with a previous reference [ 17 ]. This is an iridoid glycoside that bears two glucose units at C-1 and C-5 linked via O-glycosidic bonds and its presence in several Sideritis taxa has been reported earlier [ 1 , 15 , 20 , 21 , 22 ]; this is the first report of its occurrence in SCP.…”
Section: Resultsmentioning
confidence: 61%
“…Μelittoside ( 2 ) was isolated as a white amorphous powder and its molecular structure C 21 H 32 O 15 was determined by 1 H- & 13 C-NMR, MS, and UV-vis spectra ( Table S2 and Figures S4–S7 ), which agreed with a previous reference [ 17 ]. This is an iridoid glycoside that bears two glucose units at C-1 and C-5 linked via O-glycosidic bonds and its presence in several Sideritis taxa has been reported earlier [ 1 , 15 , 20 , 21 , 22 ]; this is the first report of its occurrence in SCP.…”
Section: Resultsmentioning
confidence: 61%
“…Concerning the isolated phenolic derivatives, compounds 27 and 30 – 33 were reported in previous studies on various Sideritis species [ 49 , 51 , 52 ], whereas compounds 28 and 29 were not found before in the specific genus. However, the constituents 28 – 33 were isolated for the first time in S. euboea .…”
Section: Resultsmentioning
confidence: 73%
“…To the best of our knowledge, the presence of apigenin 7- O -p-coumaroyl-glucosides ( 10 – 13 ) is mentioned for the first time in S. euboea . Though, apigenin 7- O -[3′′- O - trans -p-coumaroyl]- β - d -glucopyranoside ( 10 ) is found for the second time in genus Sideritis [ 49 ]. The 1 H-NMR spectra of all the isolated apigenin derivatives are presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…perfoliata with those of S. cypria, we compared them with NMR spectra of previously isolated compounds from our works in Sideritis spp. [5,8,9,12,13]. Through the screening of the 1 H-NMR spectra of different compounds, we carefully noticed that the main different hydrogen signals in the spectrum of infusion of S. perfoliata subsp.…”
Section: Resultsmentioning
confidence: 99%
“…perfoliata are used in traditional medicine as agents for various ailments such as stomach discomforts, respiratory disorders, influenza, and common cold [3]. Previous studies on extracts and infusions of these species revealed their rich nutrition and phytochemical profiles, as well as their great in vitro biological effects, including antioxidant, anti-inflammatory, antimicrobial, and cytotoxic activities [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%